Penerapan Metode The Power of Two Untuk Meningkatkan Kualitas Pembelajaran Sejarah Kebudayaan Islam (SKI) - Mahayyun, Shofria Ihda; Jannah, Siti Nur; Firdausah, Rifa'atul; Firmannur, Maulana Zunan (AL-BURHAN, 2024)
This research is a type of Classroom Action Research by applying The Power of Two learning to class XI students at MAN 1 Pati. The aim of this research is to find out: 1) improve student learning outcomes through learning the power of two, 2) improve the quality of SKI learning through learning the power of two. The research was carried out in two cycles, where the activities of each cycle consist of planning, action, observation, evaluation and reflection. Student learning outcomes have increased from pre-test, post-test cycle 1, to post-test cycle 2. This can be seen from the average student score of 59.7 (pre-test), increasing to 66.8 (post-test cycle 1), and increased again to 79.5 (post test cycle 2). Improvements in student learning outcomes can also be seen from learning completeness with Minimum Completeness Criteria (KKM). It was proven in the pre-test results, of the 36 students who took the test, only 6 students completed their studies. With a learning completion percentage of 22.2%. Increasing the results of post test cycle 1, of the 36 students who took the test, there were 20 students who completed their studies. With a learning completion percentage of 55.5%. It increased again in the results of post test cycle 2, of the 36 students who took the test, there were 32 students who completed their studies. With a learning completion percentage of 88%Keyword: The Power of two, Learning Method, Quality of SKI Learning, MAN 1 Pati